Spontaneous ovarian and intrauterine non-viable heterotopic pregnancy at 12 weeks of gestation: A case report - Gulan Maree; Sozan Mohammad; Zuhur Moualla; Lynn Alshoumary; Rouba Makhos; Ahmad Alfarra (Elsevier, 2022)
Introduction: Spontaneous heterotopic pregnancy is a clinical condition in which both intrauterine and extrauterine pregnancies occur simultaneously. An ectopic pregnancy in the ovary is extremely rare in the absence of risk factors. Case presentation: A 37-year-old woman presented at 12 weeks of gestation with complaints of abdominal pain and intermittent bleeding. A transvaginal and pelvic ultrasound revealed two gestations with no cardiac activity. An ovarian pregnancy was removed via laparoscopy, and an intrauterine pregnancy was removed via curettage. The patient was discharged the following day in good health. Conclusion: The ovaries are rare sites for heterotopic pregnancy. Early pelvic ultrasound during the first trimester should be routine to obtain an accurate diagnosis and proper management of such cases.